Information System of PT ABC Sales Report - Simorangkir, Yosua Novembrianto; Widodo, Adi (International Journal of Social and Management Studies, 2022)
- In compiling the sales report of the PT ABC branch requires a system that can be used in compiling a report. Usually, the preparation of sales of philately objects is done manually, which is implemented in the form of bookkeeping. The preparation of sales reports that still use the manual system makes the Office take a long time in compiling and making reports. The design of this sales report information system uses a structured analysis model, namely FOD (Flow Of Document) with a data model plus DAD (Data Flow Chart) to describe the functional model and Zero Diagram in describing the reality of sales. The software used is Microsoft Visual Basic 6.0 with Microsoft Access database. The data processed in this system include cashier data, customer data, goods data, and so on. Infield testing with the conclusion of the test results, that the system is considered good, can be learned, easy to use, with an attractive appearance, and has been following the needs of the office